1990
DOI: 10.1007/bf01974392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-benzyl-d-glucamine dithiocarbamate on renal toxicity induced by cadmium-metallothionein in rats

Abstract: The effect of N-benzyl-D-glucamine dithiocarbamate (BGD) on the renal toxicity induced by acute exposure to cadmium-metallothionein (Cd-MT) in rats was studied. Rats were injected intraperitoneally with BGD (400 mumol/kg) 6, 12, or 24 h after intraperitoneal injection of Cd-MT (1.78 mumol Cd as Cd-MT/kg) and thereafter they received three injections of BGD (400 mumol/kg) daily for 3 days. Urinary protein concentration and aspartate aminotransferase (AST) activity significantly increased 1 day after Cd-MT treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…From the data shown in Tables I and II, the selection of a single compound as the optimal agent in terms of potency is dependent upon whether the maximum removal of cadmium is desired from the kidney or the liver. The advantage of removing cadmium from the kidney lies in the fact that the initial stages of renal damage found with chronic cadmium intoxication in the rat may be reversed by treatment with dithiocarbamates such as those described here (14,15). The advantage of using a compound that removes the maximum amount of cadmium from the liver lies in the fact that this thus removes the reservoir of cadmium in the liver which would otherwise be trans- ported to the kidneys upon cessation of treatment.…”
Section: Discussionmentioning
confidence: 96%
“…From the data shown in Tables I and II, the selection of a single compound as the optimal agent in terms of potency is dependent upon whether the maximum removal of cadmium is desired from the kidney or the liver. The advantage of removing cadmium from the kidney lies in the fact that the initial stages of renal damage found with chronic cadmium intoxication in the rat may be reversed by treatment with dithiocarbamates such as those described here (14,15). The advantage of using a compound that removes the maximum amount of cadmium from the liver lies in the fact that this thus removes the reservoir of cadmium in the liver which would otherwise be trans- ported to the kidneys upon cessation of treatment.…”
Section: Discussionmentioning
confidence: 96%
“…The parameter X x may affect the overall cadmium mobilization process either via its effect on the interaction of chelating agent and transport protein or on some intracellular process more directly involved in the mobilization of cadmium. 199213;Kojima et al 1989Kojima et al & 1990. Electrically neutral chelating agents which possess appreciable lipid solubility, such as BAL, have been known for some time to be capable of reaching intracellular sites via movement across the lipid portion of the cellular membrane (Shaikh & Lucis 1972;Cherian 1980).…”
Section: 7mentioning
confidence: 99%
“…Such information is only available from longer term studies, such as those which have been carried out on mice and rats with dithiocarbamate cadmium mobilizing chelating agents (Gale el al. 199213;Kojima et al 1989Kojima et al & 1990. In such studies it has been demonstrated that the administration of appropriate dithiocarbamates results in a significant reduction of both renal cadmium levels and renal damage as measured by both proximal tubule histopathology and the urinary levels of protein, aspartate and amino acids.…”
Section: 7mentioning
confidence: 99%
“…Chronic cadmium intoxication is characterized by the presence of long-lived deposits of cadmium, especially in the liver and the kidney where they ultimately produce symptoms such as progressive renal failure (1)(2)(3). The possibilities for the development of a clinical treatment for chronic cadmium intoxication have been increased in recent years by the development of chelating agents specifically for the purpose of removing this metal from its intracellular deposits in the liver and the kidney (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). These compounds have all been either dithiocarbamates or dithiols.…”
Section: Introductionmentioning
confidence: 99%